THE ESSENCE OF THE CASH FLOW STATEMENT AND THE NECESSITY FOR IMPROVING ITS PREPARATION - Saidmurad Yahyoevich Atamurodov (Scholar Express Journals, 2024)
This article covers the essence of the cash flow statement and the need to improve its preparation. The regulatory framework for drawing up the cash flow statement is studied and conclusions are made. Based on international practice and experience, proposals and recommendations for improving the preparation of the cash flow statement are developed.
Keywords: cash flow statement; operating activities; investment activities